The Prevalence of Bullying Cases in High Schools Medan City - Nasution, Salsabila; Firman, Firman; Afdal, Afdal; Zaky, Naufal (Universitas Negeri Padang, 2024)
Bullying in schools is a global phenomenon that is increasingly receiving serious attention from various parties, including the government, educators, and the community. This study aims to analyze the prevalence and characteristics of bullying among high school students in Medan City, as well as the factors that influence the incidence of bullying. The method used in this study is quantitative with a random sampling technique of 300 students spread across several high schools in Medan City. The questionnaire in this study was adapted from the Olweus Bullying Questionnaire (OBQ) 2007 as a data collection tool and then analyzed using excel software to identify victims of bullying, students' experiences related to the type of bullying experienced and its frequency. The results showed that 41.3% of students (124 out of 300 students surveyed) reported having been victims of bullying. The majority of victims were female students (78 students), with the most commonly experienced form of bullying being nonverbal bullying (social exclusion and spreading rumors). The research found that females were more vulnerable to nonverbal bullying, while males experienced verbal and physical bullying more frequently